Notes PDE Pt4
Notes PDE Pt4
Notes PDE Pt4
Part IV
a2 uxx = utt
The two boundary conditions reflect that the two ends of the string are
clamped in fixed positions. Therefore, they are held motionless at all time.
The equation comes with 2 initial conditions, due to the fact that it contains
the second partial derivative term utt. The two initial conditions are the
initial (vertical) displacement u(x, 0), and the initial (vertical) velocity
ut(x, 0), both are arbitrary functions of x alone. (Note that the string is
merely the medium for the wave, it does not itself move horizontally, it only
vibrates, vertically, in place. The resulting wave form, or the wave-like
“shape” of the string, is what moves horizontally.)
We first let u(x, t) = X(x)T(t) and separate the wave equation into two
ordinary differential equations. Substituting uxx = X ″ T and utt = X T ″ into
the wave equation, it becomes
a2 X ″ T = X T ″.
X ′′ T ′′
=
X a2 T
X ′′ T ′′
= =−λ
X a2 T
X ′′
=−λ → X ″ = −λX → X ″ + λX = 0,
X
T ′′
=−λ → T ″ = −a2 λ T → T ″ + a2 λ T = 0.
a2 T
The boundary conditions also separate:
T ″ + a2 λ T = 0.
X ″ + λX = 0, X(0) = 0, X(L) = 0.
We have already solved this eigenvalue problem, recall. The solutions are
n2 π 2
Eigenvalues: λ= 2 , n = 1, 2, 3, …
L
nπ x
Eigenfunctions: X n = sin , n = 1, 2, 3, …
L
Next, substitute the eigenvalues found above into the second equation to find
T(t). After putting eigenvalues λ into it, the equation of T becomes
n 2π 2
T ′′ + a
2
T =0.
L2
anπ
r=± i.
L
Thus, the solutions are simple harmonic:
anπ t anπ t
Tn (t ) = An cos + Bn sin
L L , n = 1, 2, 3, …
Multiplying each pair of Xn and Tn together and sum them up, we find the
general solution of the one-dimensional wave equation, with both ends fixed,
to be
There are two sets of (infinitely many) arbitrary coefficients. We can solve
for them using the two initial conditions.
Set t = 0 and apply the first initial condition, the initial (vertical)
displacement of the string u(x, 0) = f (x), we have
∞
nπ x
u ( x,0) = ∑ ( An cos(0) + Bn sin(0) ) sin
n =1 L
∞
nπ x
= ∑ An sin = f ( x)
n =1 L
Therefore, we see that the initial displacement f (x) needs to be a Fourier sine
series. Since f (x) can be an arbitrary function, this usually means that we
need to expand it into its odd periodic extension (of period 2L). The
coefficients An are then found by the relation An = bn, where bn are the
corresponding Fourier sine coefficients of f (x). That is
nπ x
L
2
An = bn = ∫ f ( x ) sin dx .
L0 L
Notice that the entire sequence of the coefficients An are determined exactly
by the initial displacement. They are completely independent of the other
sequence of coefficients Bn, which are determined solely by the second
initial condition, the initial (vertical) velocity of the string. To find Bn, we
differentiate u(x, t) with respect to t and apply the initial velocity,
ut(x, 0) = g(x).
∞
anπ nπ x
ut ( x,0) = ∑ Bn sin = g ( x) .
n =1 L L
We see that g(x) needs also be a Fourier sine series. Expand it into its odd
periodic extension (period 2L), if necessary. Once g(x) is written into a sine
series, the previous equation becomes
∞
anπ nπ x ∞
nπ x
ut ( x,0) = ∑ Bn sin = g ( x) = ∑ bn sin
n =1 L L n =1 L
Therefore,
nπ x
L
L 2
Bn =
anπ
bn =
anπ ∫ g ( x) sin
0
L
dx .
nπ x
L
2
An = ∫ f ( x ) sin dx , n = 1, 2, 3, …
L0 L
Therefore,
∞
anπ t nπ x
u ( x, t ) = ∑ An cos sin
n =1 L L .
Use the product formula sin(A) cos(B) = [sin(A − B) + sin(A + B)] / 2, the
solution above can be rewritten as
1 ∞ nπ ( x − at ) nπ ( x + at )
u ( x, t ) = ∑ An sin + sin
2 n =1 L L
In which F(x) is the odd periodic extension (period 2L) of the initial
displacement f (x).
*
Jean le Rond d”Alembert (1717 – 1783) was a French mathematician and physicist. He is perhaps best
known to calculus students as the inventor of the Ratio Test for convergence.
nπ x
L
2
Bn =
anπ ∫
0
g ( x) sin
L
dx , n = 1, 2, 3, …
Therefore,
∞
anπ t nπ x
u ( x, t ) = ∑ Bn sin sin
n =1 L L .
2
First note that a = 9 (so a = 3), and L = 5.
∞
3nπ t 3nπ t nπ x
u ( x, t ) = ∑ An cos + Bn sin sin
n =1 5 5 5 .
A5 = b5 = 4,
A10 = b10 = −1,
A25 =b25 = −3,
An = bn = 0, for all other n, n ≠ 5, 10, or 25.
Indeed, you could easily verify (do this as an exercise) that the solution
obtained this way is identical to our previous answer. Just apply the addition
formula of sine function ( sin(α ± β) = sin(α)cos(β) ± cos(α)sin(β) ) to each
term in the above solution and simplify.
2
As in the previous example, a = 9 (so a = 3), and L = 5.
Therefore, the general solution remains
∞
3nπ t 3nπ t nπ x
u ( x, t ) = ∑ An cos + Bn sin sin
n =1 5 5 5 .
nπ x nπ x
L 5
2 2
Bn =
anπ ∫
0
g ( x) sin
L
dx =
3nπ ∫0
4 sin
5
dx
80
, n = odd
= 3n 2π 2
0 , n = even
Therefore,
∞
80 3( 2n − 1)π t ( 2n − 1)π x
u ( x, t ) = ∑ sin sin
n =1 3( 2n − 1) 2 π 2 5 5 .
In addition to the fact that the constant a is the standing wave’s propagation
speed, several other observations can be readily made from the solution of
the wave equation that give insights to the nature of the solution.
To reduce the clutter, let us look at the form of the solution when there is no
initial velocity (when g(x) = 0). The solution is
∞
anπ t nπ x
u ( x, t ) = ∑ An cos sin
n =1 L L .
The sine terms are functions of x. They described the spatial wave patterns
(the wavy “shape” of the string that we could visually observe), called the
normal modes, or natural modes. The frequencies of those sine waves that
we could see, nπ / L, are called the spatial frequencies of the wave. They are
also known as the wave numbers. It measures the angular motion, in radians,
per unit distance that the wave travels. The “period” of each spatial (sine)
function, 2/( nπ / L) = 2L / n, is the wave length of each term. Meanwhile, the
cosine terms are functions of t, they give the vertical displacement of the
string relative to its equilibrium position (which is just the horizontal, or the
x-axis). They describe the up-and-down vibrating motion of the string at
each point of the string. These temporal frequencies (the frequencies of
functions of t; in this case, the cosines’) are the actual frequencies of
oscillating motion of vertical displacement. Since this is the undamped
wave equation, the motion of the string is simple harmonic. The frequencies
of the cosine terms, anπ / L (measured in radians per second), are called the
natural frequencies of the string. In a string instrument, they are the
frequencies of the sound that we could hear. The corresponding natural
periods (= 2π / natural frequency) are, therefore, T = 2L / an.
For n = 1, the observable spatial wave pattern is that of sin(πx / L). The wave
length is 2L, meaning the length L string carries only a half period of the
sinusoidal motion. It is the string’s first natural mode. The first natural
For n = 2, the spatial wave pattern is sin(2πx / L) is the second natural mode.
Its wavelength is L, which is the length of the string itself. The second
natural frequency of oscillation, 2aπ / L, is also called the second harmonic,
or the first overtone, of the string. It is exactly twice of the string’s
fundamental frequency; hence its wavelength (= L) is only half as long.
Acoustically, it produces a tone that is exactly one octave higher than the
first harmonic. For n = 3, the third natural frequency, 3aπ / L, is also called
the third harmonic, or the second overtone. It is 3 times larger than the
fundamental frequency and, at a 3:2 ratio over the second harmonic, is
situated exactly halfway between the adjacent octaves (at the second and the
fourth harmonics). The fourth natural frequency (fourth harmonic/ third
overtone), 4aπ / L, is four times larger than the fundamental frequency and
twice of that the second natural frequency. The tone it produces is, therefore,
exactly 2 octaves and 1 octave higher than those generated by the first and
second harmonics, respectively. Together, the sequence of all positive
integer multiples of the fundamental frequency is called a harmonic series
(not to be confused with that other harmonic series that you have studied in
calculus).
The motion of the string is the combination of all its natural modes, as
indicated by the terms of the infinite series of the general solution. The
presence, and magnitude, of the nature modes are solely determined by the
(Fourier sine series expansion of) initial conditions.
Lastly, notice that the “wavelike” behavior of the solution of the undamped
wave equation, quite unlike the solution of the heat conduction equation
discussed earlier, does not decrease in amplitude/intensity with time. It
never reaches a steady state (unless the solution is trivial, u(x, t) = 0, which
occurs when f (x) = g(x) = 0). This is a consequence of the fact that the
undamped wave motion is a thermodynamically reversible process that
needs not obey the second law of Thermodynamics.
Second natural mode (oscillates at the 2nd natural frequency / 2nd harmonic):
Third natural mode (oscillates at the 3rd natural frequency / 3rd harmonic):
∞
anπ t anπ t nπ x
u ( x, t ) = ∑ An cos + Bn sin sin
n =1 L L L .
nπ x
L
2
An = ∫ f ( x ) sin dx , and
L0 L
nπ x
L
2
Bn =
anπ ∫ g ( x) sin
0
L
dx .
(b) u(x, 0) = 0,
ut(x, 0) = 6.
(c) u(x, 0) = 0,
ut(x, 0) = 12sin(2x) − 16sin(5x) + 24sin(6x).
4. Verify that the D’Alembert solution, u(x, t) = [F(x − at) + F(x + at)] / 2,
where F(x) is an odd periodic function of period 2L such that F(x) = f (x) on
the interval 0 < x < L, indeed satisfies the initial-boundary value problem by
checking that it satisfies the wave equation, boundary conditions, and initial
conditions.
a2 uxx = utt + γ ut + k u.
a2 uxx = utt + γ ut , γ ≠ 0.
Suppose boundary conditions remain as the same (both ends fixed): (0, t) = 0,
and u(L, t) = 0.
a2X ″ T = X T ″ + γ X T ′,
2
Divide both sides by a X T , and insert a constant of separation:
X ′′ T ′′ + γ T ′
= 2
= −λ .
X a T
X ″ = −λ X → X ″ + λ X = 0,
T ″ + γ T ′ = − a2 λ T → T ″ + γ T ′ + a2 λ T = 0.
T ″ + γ T ′ + α2 λ T = 0 .
n2 π 2
Eigenvalues: λ= 2 , n = 1, 2, 3, …
L
nπ x
Eigenfunctions: X n = sin
L , n = 1, 2, 3, …
Example: A flexible string of length L has its two ends firmly secured.
Assume there is no damping. Suppose the string has a weight density of 1
Newton per meter. That is, it is subject to, uniformly across its length, a
constant force of F(x, t) = 1 unit per unit length due to its own weight.
Let u(x, t) be the vertical displacement of the string, 0 < x < L, and at any
time t > 0. It satisfies the nonhomogeneous one-dimensional undamped
wave equation:
a2 uxx + 1 = utt.
The usual boundary conditions u(0, t) = 0, and u(L, t) = 0, apply. Plus the
initial conditions u(x, 0) = f (x) and ut(x, 0) = g(x).
−1 2
v( x) = x + C1 x + C 2 .
2a 2
−1 2 L
v( x) = x + x.
2a 2 2a 2
Comment: Thus, the sag of a wire or cable due to its own weight can be
seen as a manifestation of the steady-solution of the wave equation. The sag
is also parabolic, rather than sinusoidal, as one might have reasonably
assumed, in nature.
We can then subtract out v(x) from the equation, boundary conditions,
and the initial conditions (try this as an exercise), the transient
solution w(x, t) must satisfy:
∞
anπ t anπ t nπ x
w( x, t ) = ∑ An cos + Bn sin sin
n =1 L L L .
u ( x, t ) = v( x) + w( x, t )
−1 2 L ∞
anπ t anπ t nπ x
= 2 x + 2 x + ∑ An cos + Bn sin sin
2a 2a n =1 L L L
nπ x
L
2
An = ∫ ( f ( x) − v( x) )sin dx , and
L0 L
nπ x
L
2
Bn =
anπ ∫
0
g ( x) sin
L
dx .
Note: Since the velocity ut(x, t) = vt(x) + wt(x, t) = 0 + wt(x, t) = wt(x, t). The
initial velocity does not need any adjustment, as ut(x, 0) = wt(x, 0) = g(x).
The last type of the second order linear partial differential equation in 2
independent variables is the two-dimensional Laplace equation, also called
the potential equation. Unlike the other equations we have seen, a solution
of the Laplace equation is always a steady-state (i.e. time-independent)
solution. Indeed, the variable t is not even present in the Laplace equation.
The Laplace equation describes systems that are in a state of equilibrium
whose behavior does not change with time. Some applications of the
Laplace equation are finding the potential function of an object acted upon
by a gravitational / electric / magnetic field, finding the steady-state
temperature distribution of the (2- or 3-dimensional) heat conduction
equation, and the steady-state flow of an ideal fluid.
Since the time variable is not present in the Laplace equation, any problem
of the Laplace equation will not, therefore, have an initial condition. A
Laplace equation problem has only boundary conditions.
Let u(x, y) be the potential function at a point (x, y), then it is governed by
the two-dimensional Laplace equation
uxx + uyy = 0.
Similarly, suppose u(x, y, z) is the potential function at a point (x, y, z), then it
is governed by the three-dimensional Laplace equation
Now let us take a step back and see the bigger picture: how the
homogeneous heat conduction and wave equations are structured, and how
they are related to the Laplace equation of the same (spatial) dimension.
∇2 u = uxx + uyy.
(As we have just noted, in the one-variable case, the Laplaian of u(x),
degenerates into ∇2 u = u″.)
α2 ∇2 u = ut,
α2 uxx = ut
α2 (uxx + uyy) = ut
a2 ∇2 u = utt,
where the constant a is the propagation velocity of the wave motion. Thus,
the homogeneous wave equations of 1-, 2-, and 3-dimension are,
respectively,
a2 uxx = utt
Now let us consider the steady-state solutions of these heat conduction and
wave equations. In each case, the steady-state solution, being independent
of time, must have all zero as its partial derivatives with respect to t.
Therefore, in every instance, the steady-state solution can be found by
setting, respectively, ut or utt to zero in the heat conduction or the wave
equations and solve the resulting equation. That is, the steady-state solution
of a heat conduction equation satisfies
α2 ∇2 u = 0,
∇2 u = 0.
uxx = 0,
uxx + uyy = 0,
X ″ Y + X Y ″ = 0,
X ″ Y = −X Y ″.
X ′′ Y ′′
=−
X Y
Now that the independent variables are separated to the two sides, we can
insert the constant of separation. Unlike the previous instances, it is more
convenient to denote the constant as positive λ instead.
X ′′ Y ′′
=− =λ
X Y
Y ′′
− =λ → Y ″ = −λ Y → Y ″ + λ Y = 0.
Y
X ″ − λX = 0, X(0) = 0,
The next step is to solve the eigenvalue problem. Notice that there is
another slight difference. Namely that this time it is the equation of Y that
gives rise to the two-point boundary value problem which we need to solve.
However, except for the fact that the variable is y and the function is Y,
rather than x and X, respectively, we have already seen this problem before
(more than once, as a matter of fact; here the constant L = b). The
eigenvalues of this problem are
n2 π 2
λ =σ = 2 ,
2
n = 1, 2, 3, …
b
nπ y
Yn = sin , n = 1, 2, 3, …
b
n 2π 2
X ′′ − X =0, X(0) = 0.
b2
n 2π 2 nπ
Its characteristic equation, r −
2
= 0 , has real roots r = ± .
b2 b
nπ − nπ
x x
X = C1 e b
+ C2 e b
.
X(0) = 0 = C1 + C2 → C2 = −C1.
nbπ x −nπ
x
X n = Cn e − e b .
eθ − e −θ
sinh θ = ,
2
nπ x
X n = K n sinh , n = 1, 2, 3, …
b
Combining the solutions of the two equations, we get the set of solutions
that satisfies the two-dimensional Laplace equation, given the specified
boundary conditions:
nπ x nπ y
u n ( x, y ) = X n ( x) Yn ( y ) = K n sinh sin ,
b b
n = 1, 2, 3, …
The general solution, as usual, is just the linear combination of all the above,
linearly independent, functions un(x, y). That is,
∞
nπ x nπ y
u ( x, y ) = ∑ K n sinh sin
n =1 b b .
To find the particular solution, we will use the fourth boundary condition,
namely, u(a, y) = f (y).
∞
anπ nπ y
u (a, y ) = ∑ K n sinh sin = f ( y)
n =1 b b
We have seen this story before. There is nothing really new here. The
summation above is a sine series whose Fourier sine coefficients are
bn = Kn sinh(anπ / b). Therefore, the above relation says that the last
boundary condition, f (y), must either be an odd periodic function (period =
2b), or it needs to be expanded into one. Once we have f (y) as a Fourier sine
series, the coefficients Kn of the particular solution can then be computed:
anπ nπ y
b
2
K n sinh = bn = ∫ f ( y ) sin dy
b b0 b
Therefore,
nπ y
b
bn 2
Kn =
anπ
=
anπ ∫ f ( y ) sin
b
dy
.
sinh b sinh 0
b b
1 1
u rr + u r + 2 uθθ = 0 .
r r
1 1
R′′Θ + R′Θ + 2 RΘ′′ = 0 .
r r
This equation above can be rewritten into two ordinary differential equations:
r2 R″ + rR′ − λR = 0,
Θ″ + λΘ = 0.
A0 ∞
u (r , θ ) = + ∑ ( An cos nθ + Bn sin nθ ) r n .
2 n =1
A0 ∞
u (k , θ ) = ( )
+ ∑ An k n cos nθ + Bn k n sin nθ = f (θ ) .
2 n =1
a0 ∞
f (θ ) = + ∑ (an cos nθ + bn sin nθ ) .
2 n =1
For a problem on the unit circle, whose radius k = 1, the coefficients An and
Bn are exactly identical to, respectively, the Fourier coefficients an and bn of
the boundary condition f (θ).